Efektifitas Pola Integrasi Faktor Kognitif, Afektif, Dan Psikomotorik Terhadap Prilaku Positif - Hasim Ashari (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract: Every human being has innate potential, which is both good and bad potential. However, this innate potential cannot develop by itself, meaning that it requires a well-organized system. In Indonesia the education system with good management in the form of educational institutions, such as formal, non-formal and informal educational institutions. This educational institution is a reflection of the implementation of Law Number 20 Year 2003 concerning the National Education System. The fact is that the government and all its efforts in improving the quality of educational institutions have not been able to optimally create superior products that can compete nationally and internationally. Not only that, the output produced is quite a lot that is not in accordance with the realm and goals of education itself, namely creating a true human being, a human being with a whole human personality. This article will discuss in detail the effectiveness of integrating cognitive, affective, and psychomotor factors in achieving positive behavior amid globalization and industry 4.0. the type of research is qualitative with the type of literature approach, which is research centered on literature study.